The Reliability Investigation on the Assessment Criteria for Local Metal Loss Based on API 579-1/ASME FFS-1 - SAKAI, Shinsuke; IZUMI, Satoshi; KAIDA, Takuyo; MOGAMI, Yuichi (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series A, 2011)
In order to rationalize the safety margin of pressurized components subject to local metal loss, we applied a probabilistic reliability method. The modeling of the local metal loss is based on API 579-1/ASME FFS-1 and we investigated the safety margin for the pressure equipment subjected to local metal loss utilizing the actual corrosion rate data. Probabilities of failure of both shallow metal loss and deep metal loss were calculated. These results showed the relation between time until next inspection and probability of failure was cleared. We also analyzed the sensitivity of an assessment curve based on the reliability index for local metal loss. The reliability-based assessment curve was available regardless of COV of the shape of metal loss.